Madrasah Diniyah di Tengah Kampung PSK - A.M Wibowo (Edukasia Islamika : Jurnal Pendidikan Islam, 2016)
Recently, the rate of young marriages in Indonesia is getting higher. It is necessary to have some efforts in restraining it such as delivering an informal education through madrasah diniyah. The aim of this study is to find out the role of Madrasah Diniyah Miftahul Hidayah in restraining the rate of young marriages and prostitution in a village of Bandar district, Batang regency, Central Java. By using case study approach, the research came to three conclusions. First, Madrasah Diniyah Miftahul Hidayah is an informal educational institution which tries to anticipate young marriage and prevent prostitution. Second, one of the efforts done in restraining them is by changing the curriculum, the teachers’ and students’ mindset as well. Finally, the obstructions faced in restraining them is the strong opinion of the society that the more girls get married earlier, more prestigious she is.